2021
DOI: 10.1563/aaid-joi-d-20-00411
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of the Primary Stability of Straumann BLX Implant Design Using an In Vitro Sinus Lift–Simultaneous Implant Insertion Model

Abstract: Straumann ®  BLX is a novel implant system, which has been proclaimed to provide an ideal primary stability in all types of bone. In the current study, the primary stability of Straumann ®  BLX implant systems with Straumann ®  tapered effect (TE) implants have been comparatively assessed in bovine ribs by using a simultaneous sinus elevation and implant insertion model.  In the study group, BLX (4.0 x 12 mm), TE (4.1 x 12 mm), BLX (4,5 x 12 mm) and TE (4.8 x 12 mm) were placed in each bony window, which resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…A recent previous study that compared the primary stability between BLX implants and TE implants in a similar model (sinus lift-simultaneous implant insertion model) indicated that TE implants with wider diameter showed higher ISQ values. [24] The difference between this previous study and the present study was bone condition for implant placement. The bone specimens in this previous study was consisted of cortical bone and cancellous bone, and it was suggested that TE implants could indicated higher ISQ values because TE implants with tapered neck design could achieve higher primary stability at cortical bone.…”
Section: Discussionmentioning
confidence: 54%
“…A recent previous study that compared the primary stability between BLX implants and TE implants in a similar model (sinus lift-simultaneous implant insertion model) indicated that TE implants with wider diameter showed higher ISQ values. [24] The difference between this previous study and the present study was bone condition for implant placement. The bone specimens in this previous study was consisted of cortical bone and cancellous bone, and it was suggested that TE implants could indicated higher ISQ values because TE implants with tapered neck design could achieve higher primary stability at cortical bone.…”
Section: Discussionmentioning
confidence: 54%
“…Current study has also particularly showed that AMSCs treatment could increase the histological density of the augmented area; however, we think that the difference would not influence the treatment modality. However, a further study might focus on the effect of this difference in terms of mechanical anchorage of the dental implant and thereby assessing the possibility of an immediate loading protocol [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that multiple factors were associated with primary stability (MIT and ISQ values), even in an SFE simulated model that was designed to evaluate primary stability with a limited bone volume. A recent previous study that compared the primary stability between BLX implants and TE implants in a similar model (sinus lift-simultaneous implant insertion model) indicated that TE implants with wider diameter showed higher ISQ values [ 24 ]. The difference between this previous study and the present study was bone condition for implant placement.…”
Section: Discussionmentioning
confidence: 99%